Enhanced Network Connectivity And Node Lifetime Techniques In Wireless Sensor Networks - Al-Saidi, Ali Shanon Aiyal (2013)
Low-cost sensors that may be integrated to form Wireless Sensor Networks (WSNs) have received increased research attention for their potential application in environmental monitoring, healthcare, and defence, among others. Connectivity is essential in WSNs. It represents the ability of a member node to communicate with other nodes within a network either through direct transmission or multi-hop relays. Low connectivity is a result of the network being broken up into different and disconnected groups of nodes. Whether they are dispersed from the air or are installed manually, nodes may still have a sparsely dense distribution. The limited radio range of the nodes can also cause the network to partition into disjoint groups, a process that interrupts or completely prevents communication. This dissertation proposes an Intelligent Multi-Hop Cluster Transmission of Information (IMHCTI) protocol which integrates a Mathematical Stochastic Cross-Layer (MSCL) model with the proposed MHCTI protocol to improve network connectivity and enhance network lifetime. The MHCTI protocol is based on network clustering coherent-cooperative transmission fields from closely spaced wireless nodes, to improve the data transmission distance range and to address the problem of poor network connectivity.